Validation of a inertial movement unit with a linear encoder to evaluate strength and power - Raúl Fernández Llopez; Ana María De Benito Trigueros; Enric Cosme Llópez; Carlos Pablos Abella (Asociación Española de Ciencias del Deporte, 2019)
The object of this study was to find out the evaluation and reliability of an inertial movement unit (IMU), based on the TITAN (rO2 Sport Technology and Consulting, Valencia, Spain) system, measuring the variables of sports performance. A linear encoder T-Force (Ergotech System, Murcia, Spain) was used to compare data obtained. 10 voluntary subjects with previous experience of strength training in the study participated. They carried out a total of 200 times bench press in concentric phase, 50% and 70% of individual body weight. The variables analyzed were: maximum speed, maximum acceleration, maximum strength and maximum power peak. Models of linear regression with an independent variable (T-Force data) and a dependant variable (TITAN data) were applied. The assumed independence of error was contrasted by way of a Durban-Watson trial. Partial self correlations were calculated with a significant level p≤0.05. The existence of interclass correlations between the averages of both apparatus, ranging between 0.95 and 0.99 was conformed. In conclusion, the TITAN system could be a valid system to measure maximum velocity, maximum acceleration, maximum strength and maximum power peak during the bench press trial. Therefore, this system based on IMU, could be a valuable tool for the evaluation of strength and power training in the execution of this movement.